Daily life of women in Chaucer's England - Edwards, Jennifer C. ca. 20./21. Jh (Greenwood, 2022)
"This book examines the lives of women in England during the fourteenth and fifteenth centuries, a period known as the late Middle Ages"--
Keywords: Geschichte 1350-1400; Alltag; Frau; England; Women / History / Middle Ages, 500-1500; Women / England / History / To 1500; Women / England / Social conditions; Femmes / Histoire / 500-1500 (Moyen Âge); Femmes / Angleterre / Histoire / Jusqu'à 1500; Femmes / Angleterre / Conditions sociales; Women; Women / Middle Ages; Women / Social conditions; To 1500; History